DINAMIKA PERDAGANGAN SENJATA RINGAN INDONESIA DI KANCAH GLOBAL TAHUN 2014-2019 - Yusro, Muhammad Rizki; Harimurti, Sigid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2022)
The purpose of this article is to analyze the dynamics of Indonesia in the international arms trade. The arms trade continues to show a gradual increase driven by the economic interests of each country in addition to security interests. Arms trade is an important factor in its contribution to economic growth through exports and imports of defense equipment, although it is interesting to know how the dynamics of Indonesia's arms trade in the global arena in the military industry can facilitate Indonesia's main goal in international arms trade, namely as a leading arms supplier in the world. world. The research method used in this study is a qualitative method. In conducting this research in order to facilitate the analysis, the author uses the concept of the Military Industrial Complex with a writing method in the form of descriptive analysis and in the process of analyzing and interpreting the data used the process of data reduction and drawing conclusions. At the end of this article, the author finds that the dynamics of Indonesia's activeness in the global arms trade is still dominated by its role as an arms importer, although over time, Indonesia continues to show developments regarding the implementation of its goal to become the world's leading arms exporter. However, despite these facts, there are several main problems that need to be faced by Indonesia, namely those related to the need for structural changes in the three main pillars of the defense industry, the allocation of the defense budget in the field of research and development, and collaboration in developing the defense industry. Keywords: Arms Trade, Military Industrial Complex, Universal Defense Strategy